Research on End AC Loss and Electromagnetic Vibration of Superconducting Machine Based on 3-D H-Formulation - Luo, Chao; Shou, Jiabo; Ma, Jien; Chao, Jie; Fang, Youtong (IEEE transactions on applied superconductivity, 2025)
In electrified drive systems, machine vibration has become as critical performance as power density. However, limited research has focused on the vibration characteristics of superconducting rotary machines. Most studies rely on 2-D numerical models that overlook the complex stacked racetrack superconducting coil end in the machine. The ac loss at the end in the complex and strong magnetic field needs precise calculation, as it subjects the stator end to significantly larger electromagnetic forces than those in conventional machines. It is crucial to analyze the magnetic field and coil vibrations caused by these forces and to investigate various end-fixation strategies. This article presents a comprehensive 3-D model of superconducting machines using the H-formulation, enabling accurate determination of electromagnetic performance under varying current conditions. The critical current density and ac losses in the superconducting coil ends are analyzed. This study further investigates the 3-D magnetic field distribution and the resulting electromagnetic vibrations, particularly in the stator armature windings. Significant electromagnetic forces are observed at the stator winding ends, leading to excessive vibration and deformation under rated conditions. The research also explores various end-fixation methods to mitigate these effects, ultimately enhancing the stability and performance of superconducting machines in next-generation low-carbon transportation systems.